The Added Value of Cerebral Imaging in Patients With Pyogenic Spinal Infection - Behmanesh, Bedjan; Gessler, Florian; Kessel, Johanna; Keil, Fee; Seifert, Volker; Bruder, Markus; Setzer, Matthias (Frontiers in Neurology, 2021)
Background: The incidence of pyogenic spinal infection has increased in recent years. In addition to treatment of the spinal infection, early diagnosis and therapy of coexisting infections, especially of secondary brain infection, are important. The aim of this study is to elucidate the added value of routine cerebral imaging in the management of these patients. Methods: This was a retrospective single-center study. Cerebral imaging consisting of cerebral magnetic resonance imaging (cMRI) was performed to detect brain infection in patients with a primary pyogenic spinal infection. Results: We analyzed a cohort of 61 patients undergoing cerebral imaging after diagnosis of primary pyogenic spinal infection. The mean age in this cohort was 68.7 years and the gender distribution consisted of 44 males and 17 females. Spinal epidural abscess was proven in 32 (52.4%) patients. Overall positive blood culture was obtained in 29 (47.5%) patients, infective endocarditis was detected in 23 (37.7%) patients and septic condition at admission was present in 12 (19.7%) Patients. Coexisting brain infection was detected in 2 (3.3%) patients. Both patients revealed clinical signs of severe sepsis, reduced level of consciousness (GCS score 3), were intubated, and died due to multi-organ failure. Conclusions: Brain infection in patients with spinal infection is very rare. Of 61 patients with pyogenic spinal infection, two patients had signs of cerebral infection shown by imaging, both of whom were in a coma (GCS 3), and sepsis.